МУСТАҚИЛЛИК ДАВРИ ЎЗБЕК ДРАМАТУРГИЯСИДА АМИР ТЕМУР ОБРАЗИНИНГ БАДИИЙ ТАЛҚИНИ - Аҳмедова, В.А. (SCIENCE and SOCIETY, 2019)
The article describes the historical-legal, axiological, literary and educational background of Uzbek dramaturgy of the independence period time. The achievements and shortcomings in the works with the image of Amir Temur have been researched.